Exigência de proteína digestível, para alevinos de pacu (Piaractus mesopotamicus) alimentados com rações a base de farelo de soja e milho - Neves, Milene (2013)
The objective of this study was to. Four diets with increasing levels of digestible protein (18, 22, 26 and 30 %) based on products of plant origin were evaluated. The fry were housed in 50L hapas which were inside 1000L tanks in the greenhouse. The temperature and, dissolved oxygen were daily verified and pH was weekly verified. The fry were fed three times a day (7:30a.m., 12: 30p.m. and 5:30p.m ) after the last feeding and removal of food debris feces was performed with subsequent replacement of the water system , and after weighing the pots ration to measure consumption . The experimental design was randomized blocks with six tanks 1000L (repetitions) with four 50L hapas tanks within these treatments (18, 22, 26 and 30% of digestible protein). Each hapa settled 10 fingerlings. The fry pacu that were previously weighed batch of water 10 (9.49g ± 0.04g average weight per fish), the overall length of 8.025cm, 6.28cm gage length, height and width of 3.005 cm and 0.56 cm. The measurements were obtained by averaging done after the initial biometrics. At the end of the experiment, a quadratic effect (p<0.01) for the average final weight, standard length, total length, height and width was observed. For vestments of zootechnical performance the feed conversion ratio and survival were evaluated, and for these parameters were those who had the significance of apparent feed conversion showed a quadratic effect (p<0.05). After expiration of the trial period the fry were slaughtered and their carcasses submitted to laboratory analyzes which were: crude protein, ether extract, moisture and ash. After that the results were submitted to the same simple linear regression, the mean linearly for fat and moisture. After all the analysis it was concluded that there is a point of maximum absorption of digestible protein to a higher average final weight which is 24.65%, and that the level of digestible protein obtained results for most parameters evaluated was 26% of digestible protein